Resurrecting DFBS into the Virtual Observatory - Demleitner, Markus; Knyazyan, Aram; Baghdasaryan, Daniel; Mikayelyan, Gor; Mickaelian, Areg
The Digitised First Byurakan Survey has digitised and processed about 1900 photographic plates from the objective prism surveys conducted in Byurakan by Benjamin Markarian and collaborators in the 1960ies and 1970ies. After digitization, a custom web service was built and operated first in Rome, then in Trieste. However, as astronomical data systems and standards evolved, it became desirable to update the data and build standards-compliant, Virtual Observatory services from it. This contribution reports on the challenges encountered during this migration, the solutions we chose, and the lessons to be learned. It also discusses the use of the resulting services.
Keywords: Astronomy